2023
DOI: 10.1039/d2nr06384k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of inorganic liquid gallium particle–manganese oxide composites

Abstract: Gallium (Ga) is a low melting point post-transition metal that, under mild mechanical agitation, can form micron and submicron-sized particles with combined fluid-like and metallic properties. In this work, an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…[45,46] The Ga 2p spectrum further confirms these assignments, where the BE of ≈1116.3 eV corresponds to the elemental Ga 0 of the Ga particle core, and at BE of ≈1118.51 eV can be attributed to Ga 3+ species that originates from the thin oxide layer formed during the sonication. [45,47,48] For the MPI ink (Figure 2d), the presence of two characteristic peaks at BE of ≈458.9 and ≈465 eV, indicating the chemical states of Ti 2p 1/2 and Ti 2p 3/2 , respectively, that corroborates the existence of the 4+ oxidation state of Ti ions in the MPI, as also reported elsewhere. [36,49] Besides, the presence of Fe 3+ was also identified by XPS (Figure 2e) in the MPI with the two major peaks at BE of ≈712 and ≈725 eV that can be attributed to Fe 2p 3/2 and Fe 2p 1/2 , respectively.…”
Section: Synthesis and Characterization Of Lm-mpi Compositesupporting
confidence: 87%
“…[45,46] The Ga 2p spectrum further confirms these assignments, where the BE of ≈1116.3 eV corresponds to the elemental Ga 0 of the Ga particle core, and at BE of ≈1118.51 eV can be attributed to Ga 3+ species that originates from the thin oxide layer formed during the sonication. [45,47,48] For the MPI ink (Figure 2d), the presence of two characteristic peaks at BE of ≈458.9 and ≈465 eV, indicating the chemical states of Ti 2p 1/2 and Ti 2p 3/2 , respectively, that corroborates the existence of the 4+ oxidation state of Ti ions in the MPI, as also reported elsewhere. [36,49] Besides, the presence of Fe 3+ was also identified by XPS (Figure 2e) in the MPI with the two major peaks at BE of ≈712 and ≈725 eV that can be attributed to Fe 2p 3/2 and Fe 2p 1/2 , respectively.…”
Section: Synthesis and Characterization Of Lm-mpi Compositesupporting
confidence: 87%
“…Recently, the sonochemical-assisted technique was employed to develop various types of LM-based composite particles for functional applications [36][37][38]. A recent study reported the synthesis of nano/micro-sized Ga/Ni co-catalysts for biofuel conversion to value-added byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, catalyst materials (Ni and NiO 2 ) were employed in the sonication process to decorate the surface of gallium-based particles via the ultrasonic approach [36]. In another research study, manganese oxide [37] and molybdenum oxysulfide [38] shells were developed on the gallium-based NPs via a sonochemical synthesis approach. In these methods, the highly active surface of gallium-based NPs interacts directly with the chemical agents in the presence of strong ultrasonic waves, resulting in the synthesis of unregularly deformed NPs and nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…112 Similarly, atomic-thickness hydrated MnO 2 sheets and the inorganic network of nano-MnO 2 are synthesized by an electric coupling substitution reaction between permanganate ions and EGaIn. 12,113 Additionally, 2D CuO x nanomaterials are produced by galvanic replacement between Cu(OH) 3 − and liquid Ga. 14 The electron accumulation on the Ga surface creates a reactive surface potential, driving the reduction and self-deposition of precursor metal cations. For example, significantly crystallized rhombohedral layered Bi 2 Te 3 platelets were formed when metal-based cations (specifically Bi 3+ -HTeO 2 + in acidic environments) are introduced to the smooth and oxide-free EGaIn surfaces.…”
Section: Metal Oxide Nanomaterials (2d Materials) Ga-basedmentioning
confidence: 99%